Cobalt‐Catalyzed Selective Transformation of Levulinic Acid and Amines into Pyrrolidines and Pyrrolidinones using Hydrogen. Issue 16 (25th July 2022) - Pan, Yixiao; Luo, Zhenli; Yang, Ji; Han, Jiahong; Yang, Jianbo; Yao, Zhen; Xu, Lijin; Wang, Peng; Shi, Qian
Abstract: Cobalt‐catalyzed selective transformation of levulinic acid and primary amines into pyrrolidines and pyrrolidinones under H2 has been developed. The catalyst system consisting of Co(NTf2 )2, 1, 1, 1‐tris(di(4‐methoxyphenyl)phosphinomethyl) ethane (( p ‐anisyl)triphos) and Me3 SiOTf works well for the synthesis of pyrrolidines via reductive amination/cyclization/deoxygenative reduction of amide, and using Co(NTf2 )2 /1, 1, 1‐tris(diphenylphosphinomethyl) ethane (triphos) as the catalyst under reduced hydrogen pressure results in exclusive formation of pyrrolidinones. Both aryl and alkyl primary amines are suitable substrates, and a variety of functional groups are tolerated. Meanwhile, 4‐oxo‐4‐arylbutanoic acids, 5‐oxohexanoic acid, 6‐oxoheptanoic acid, 2‐formylbenzoic acid, 2‐acetylbenzoic acid and 2′‐acetyl‐[1, 1′‐biphenyl]‐2‐carboxylic acid are also applicable, allowing for convenient access to cyclic amines and lactams with different ring size. Abstract :